Experimental demonstration of 7-femtosecond electron timing fluctuation in laser wakefield acceleration. (1st March 2022) - Huang, Kai; Jin, Zhan; Nakanii, Nobuhiko; Hosokai, Tomonao; Kando, Masaki
Abstract: We report on an experimental investigation of the jitter of electrons from laser wakefield acceleration. The relative arrival timings of the generated electron bunches were detected via electro-optic spatial decoding on the coherent transition radiation emitted when the electrons pass through a 100 μ m thick stainless steel foil. The standard deviation of electron timing was measured to be 7 fs at a position outside the plasma. Preliminary analysis suggested that the electron bunches might have durations of a few tens of femtoseconds. This research demonstrated the potential of laser wakefield acceleration for femtosecond pump–probe studies.